Through-Focus Vision Performance and Light Disturbances of 3 New Intraocular Lenses for Presbyopia Correction - Santiago Escandón-García; Filomena J. Ribeiro; Colm McAlinden; António Queirós; José M. González-Méijome (Journal of Ophthalmology)
Purpose. To compare the through-focus visual performance in a clinical population of pseudophakic patients implanted with two new trifocal intraocular lenses (IOLs) and one extended depth of focus IOL. Methods. Prospective, nonrandomized, examiner-masked case series. Twenty-three patients received the FineVision® and seven patients received the PanOptix™ trifocal IOLs. Fifteen patients received the Symfony extended depth of focus IOL. Mean age of patients was 63 ± 8 years. Through-focus visual acuity was measured from –3.00 to +1.00 D vergences. Contrast sensitivity was measured with and without a source of glare. Light disturbances were evaluated with the Light Distortion Analyzer. Results. Though-focus evaluation showed that trifocal IOLs performed significantly better at near distance (33 and 40 cm), and extended depth of focus performed significantly better at intermediate distance (1.0 m). Contrast sensitivity function with glare and dysphotopsia was similar between the three IOLs and subjective response to questionnaire showed a significantly higher score (worse performance) for the extended depth of focus IOL compared to both trifocal IOLs in the bothersome subscale (p<0.05). Conclusions. Trifocal IOLs grant better performance at near distance while extended depth of focus IOL performs better at intermediate distance. Objective dysphotopsia measured with the Light Distortion Analyzer is not reduced in extended depth of focus IOL compared to trifocal IOLs.